Clearance of interstitial fluid (ISF) and CSF (CLIC) group—part of Vascular Professional Interest Area (PIA): Cerebrovascular disease and the failure of elimination of Amyloid‐β from the brain and retina with age and Alzheimer's disease‐Opportunities for Therapy. Issue 1 (3rd August 2020) - Carare, Roxana O.; Aldea, Roxana; Agarwal, Nivedita; Bacskai, Brian J.; Bechman, Ingo; Boche, Delphine; Bu, Guojun; Bulters, Diederik; Clemens, Alt; Counts, Scott E.; de Leon, Mony; Eide, Per K.; et al.
Abstract: Two of the key functions of arteries in the brain are (1) the well‐recognized supply of blood via the vascular lumen and (2) the emerging role for the arterial walls as routes for the elimination of interstitial fluid (ISF) and soluble metabolites, such as amyloid beta (Aβ), from the brain and retina. As the brain and retina possess no conventional lymphatic vessels, fluid drainage toward peripheral lymph nodes is mediated via transport along basement membranes in the walls of capillaries and arteries that form the intramural peri‐arterial drainage (IPAD) system. IPAD tends to fail as arteries age but the mechanisms underlying the failure are unclear. In some people this is reflected in the accumulation of Aβ plaques in the brain in Alzheimer's disease (AD) and deposition of Aβ within artery walls as cerebral amyloid angiopathy (CAA). Knowledge of the dynamics of IPAD and why it fails with age is essential for establishing diagnostic tests for the early stages of the disease and for devising therapies that promote the clearance of Aβ in the prevention and treatment of AD and CAA. This editorial is intended to introduce the rationale that has led to the establishment of the Clearance of Interstitial Fluid (ISF) and CSF (CLIC) group, within the Vascular Professional Interest Area of the Alzheimer's Association International Society to Advance Alzheimer's Research and Treatment.